Thoracic aortopathy in Marfan syndrome overlaps with mechanisms seen in bicuspid aortic valve disease - Grewal, Nimrat; Dolmaci, Onur; Jansen, Evert; Klautz, Robert; Driessen, Antoine; Poelmann, Robert E. (Frontiers in Cardiovascular Medicine, 2023)
Background: Thoracic aortopathy is a serious complication which is more often seen in patients with Marfan syndrome (MFS) and patients with a bicuspid aortic valve (BAV) than in individuals with a tricuspid aortic valve (TAV). The identification of common pathological mechanisms leading to aortic complications in non-syndromic and syndromic diseases would significantly improve the field of personalized medicine. Objective This study sought to compare thoracic aortopathy between MFS, BAV and TAV individuals. Material and methods: BAV (n = 36), TAV (n = 23) and MFS (n= 8) patients were included. Ascending aortic wall specimen were studied for general histologic features, apoptosis, markers of cardiovascular ageing, expression of synthetic and contractile vascular smooth muscle cells (VSMC) and fibrillin-1 expression. Results: The MFS group showed many similarities with the dilated BAV. Both patient groups showed a thinner intima (p<0.0005), a lower expression of contractile VSMCs (p<0.05), more elastic fiber thinning (p<0.001), lack of inflammation (p<0.001) and a decreased progerin expression (p<0.05) as compared to the TAV. Other features of cardiovascular ageing differed between the BAV and MFS. Dilated BAV patients demonstrated less medial degeneration (p<0.0001), VSMC nuclei loss (p<0.0001), apoptosis of the vessel wall (p<0.03) and elastic fiber fragmentation and disorganization (p<0.001), as compared to the MFS and dilated TAV. Conclusion: This study showed important similarities in the pathogenesis of thoracic aortic aneurysms in BAV and MFS. These common mechanisms can be further investigated to personalize treatment strategies in non-syndromic and syndromic conditions.